EVALUASI KINERJA INSTALASI PENGOLAHAN AIR LIMBAH DENGAN SISTEM LUMPUR AKTIF (ACTIVATED SLUDGE) DI RUMAH PEMOTONGAN UNGGAS PENGGARON SEMARANG - Santya Nareswari; Nurjazuli Nurjazuli; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Poultry Slaughterhouse is a building that used as a place for the pultry slaughtering process. This process produces organic waste in the solid and liquid form. Poultry slaughterhouse wastewater contains some pollutant parameters including BOD, COD, TSS , and ammonia. Penggaron Poultry Slaughterhouse Wastewater that became the object of this study contains average BOD of 401 mg/l, COD at 829,601 mg/l, TSS at 502 mg/l and ammonia at 1,9738 mg/l. Penggaron Poultry Slaughterhouse already has a Wastewater Treatment Plant with an active sludge system using PAC and alum for coagulant and EM4. This study aims to evaluate the performance of wastewater treatment to reduce BOD, COD, TSS, and ammonia that being done for 3 days. The type of study is descriptive with observational and cross sectional approach. The population in this study is all wastewater produces from slaughtering activity, the sample used are some amount of both wastewater that produce from slaughtering activity and wastewater from treatment plant. The laboratory result shows that outlet wastewater parameters still higher than the standards with an average for BOD, COD, and TSS is 304 mg/l, 643,56 mg/l, and 566 mg/l. Ammonia is under the standard, 3,1232 mg/l. Based on the effectivity calculation, wastewater treatment can reducing BOD rate by 13% - 29%, COD by 8% - 29%, TSS by 43% and ammonia by 13% - 65% so can be concluded that Penggaron Poultry Wastewater Treatment is less effective for reducing BOD, COD, and amonia.